2021
DOI: 10.1158/1078-0432.ccr-20-4555
|View full text |Cite
|
Sign up to set email alerts
|

Precision Dosing of Targeted Therapies Is Ready for Prime Time

Abstract: Fixed dosing of oral targeted therapies is inadequate in the era of precision medicine. Personalized dosing, based on pharmacokinetic (PK) exposure, known as therapeutic drug monitoring (TDM), is rational and supported by increasing evidence. The purpose of this perspective is to discuss whether randomized studies are needed to confirm the clinical value of precision dosing in oncology. PK-based dose adjustments are routinely made for many drugs and are recommended by health authorities, for example, for patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 102 publications
(93 reference statements)
1
21
0
Order By: Relevance
“…The high interindividual variability in plasma concentrations found in the present work and in previous publications [ 5 , 9 , 10 , 14 ] is likely due to multiple factors, such as varying time between intake of medication and blood sampling, variable patient adherence [ 6 , 16 ], and interactions with food and/or concomitant medications (e.g., acid reducing agents) [ 6 , 17 , 18 , 19 ]. Recently, we reported higher patient satisfaction, reduced side effects and medication errors under treatment with many new oral antitumor drugs when an intensified clinical pharmacological/pharmaceutical care program is applied on top of routine clinical care [ 8 ].…”
Section: Discussionsupporting
confidence: 49%
See 2 more Smart Citations
“…The high interindividual variability in plasma concentrations found in the present work and in previous publications [ 5 , 9 , 10 , 14 ] is likely due to multiple factors, such as varying time between intake of medication and blood sampling, variable patient adherence [ 6 , 16 ], and interactions with food and/or concomitant medications (e.g., acid reducing agents) [ 6 , 17 , 18 , 19 ]. Recently, we reported higher patient satisfaction, reduced side effects and medication errors under treatment with many new oral antitumor drugs when an intensified clinical pharmacological/pharmaceutical care program is applied on top of routine clinical care [ 8 ].…”
Section: Discussionsupporting
confidence: 49%
“…Most of the oral anticancer drugs—especially protein kinase inhibitors—are prescribed in a one dose fits all approach [ 6 , 9 , 10 ]. However, several clinical studies demonstrated considerable interindividual differences in drug exposure despite identical dosing [ 5 , 9 , 10 , 11 , 12 , 13 , 14 ], which can be considered as suboptimal. Imatinib, for example, showed varying plasma concentrations by a factor of 60 [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nevertheless, more than 30% of patients will likely become resistant to targeted drugs. Therefore, it is particularly important to comprehensively study the mechanism of the occurrence and development of RC as well as the molecules involved to generate precise treatment plans for different patients (45).…”
Section: Discussionmentioning
confidence: 99%
“…For pediatric patients, another factor that makes the rapid evaluation of clinical trials difficult is the fact that dose-finding phase I studies must be conducted again from the beginning for new pediatric antitumor drugs, even for drugs that have been approved for efficacy and safety in adults. In recent years, a review of the dosing steps for pediatric patients and the individualization of drug dosages regardless of whether a pediatric population is involved have been studied, and it is expected that the results of efficacy evaluations will be obtained more quickly in the future [ 121 , 122 , 123 ].…”
Section: Regulatory Problems and Solutions For Investigating New Trea...mentioning
confidence: 99%